Feasibility of Cardiac Computed Tomography for the Evaluation of Ventricular Function in Postoperative Children With Congenital Heart Disease: Comparison With Cardiac Magnetic Resonance Imaging. Issue 4 (July 2021) - Xie, Wei-Hui; Guo, Chen; Hu, Li-Wei; Ouyang, Rong-Zhen; Yao, Xiao-Fen; Sun, Ai-Min; Qiu, Hai-Sheng; Yan, Qin; Zhu, Ya-Xin; Wang, Qian; Zhong, Yu-Min
Abstract : Objective: We explored the feasibility of cardiac computed tomography (CCT) to evaluate postoperative ventricular function in children with congenital heart disease (CHD) and evaluated the accuracy and reproducibility of CCT using cardiac magnetic resonance (CMR) as a reference. Methods: Thirty-two postoperative children with CHD (20 boys and 12 girls) who underwent CMR and CCT were enrolled. Left and right ventricular ejection fraction, end-diastolic volume, end-systolic volume, stroke volume, and cardiac index were measured using cardiac function analysis software. Cardiac function data were compared between CMR and CCT. The agreement between the 2 modalities was assessed using a Bland-Altman analysis. Intraclass correlation coefficients were used to assess intraobserver and interobserver reproducibility in CCT functional measurements. Results: All functional parameters showed no significant difference ( P > 0.05) and were well-correlated ( r > 0.5, P < 0.05) between CMR and CCT. The mean values of all ventricular function parameters in CCT were higher compared with CMR. As indicated by 95% limits of agreement, left ventricular function parameters showed a better level of agreement compared with right ventricular function parameters between the 2 modalities. Intraobserver and interobserver reproducibility were excellent in CCT measurements for all functional parameters (intraclass correlation coefficient > 0.9). Conclusions: Compared with the criterion standard of CMR, CCT is feasible for assessing postoperative ventricular function with sufficient diagnostic accuracy and reproducibility in children with CHD. In addition to its important role regarding anatomical characterization, CCT is a suitable alternative and convenient follow-up tool that can be used to functional evaluation in children who are intolerant with CMR or have contraindications to CMR.